Polymorphisms of H-ras-1 and p53 in breast cancer and lung cancer: a meta-analysis. - Weston, A (1997)
Certain polymorphic variants of H-ras-1 and p53 have been investigated for an association between inheritance and cancer risk. The results of a metaanalysis, which reviews studies of H-ras-1 rare alleles and p53 codon 72 allelic variants in breast and lung cancer, are presented. The data constituted evidence for elevated risk of both breast and lung cancer with inheritance of rare H-ras-1 alleles. Calculated population attributable risks are 0.092 and 0.037 for breast and lung cancer, respectively. The frequency of the rare H-ras-1 alleles was observed to be greater in African Americans than in Caucasians, and a specific allele (A3.5) that is common in African Americans was found only at low frequency in Caucasians. For p53 a consensus has yet to be reached. Lung cancer studies conducted in Caucasian and African-American populations have found no evidence of risk associated with the proline variant of codon 72. Two similar studies conducted in Japanese populations suggested an association between p53 genotype distribution and lung cancer risk. However, one implicates the proline allele but the other implicates the arginine allele. The frequency of the proline variant is significantly dependent on race. Frequencies have been reported for control populations of Japanese (0.347 and 0.401), Caucasian (0.295, 0.284, and 0.214), African American (0.628 and 0.527), and Mexican American (0.263).